2004
DOI: 10.4028/www.scientific.net/msf.449-452.741
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of La<sub>1-x</sub>MnO<sub>3-1.5x</sub> with Trivalent Manganese Ion

Abstract: Defect perovskite, La1-xMnO3-1.5x (x=0.00-0.10), was synthesized by conventional ceramic method and phase transition was measured by X-ray diffractometry, electrical conductivity, thermal diffusivity and thermal analysis. La1-xMnO3-1.5x (x=0.00-0.09) have single orthorhombic phase corresponding to GdFeO3 type perovskite structure at room temperature, while have rhombohedral structural at high temperature. The transition temperatures observed from electric conductivity, DSC, thermal diffusivity were mostly in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, on prolonged use of the fuel cell, poorly conducting phases such as SrZrO 3 may form at the interface of cathode and YSZ (yttria stabilized zirconia) electrolyte. Hence recently an interest is generated to study rare earth manganites without aliovalent doping at the lanthanum site in LaMnO 3 [5]. Detailed investigations on polymorphic forms, defect structure, magnetism, ionic conducting properties and catalytic behaviour of lanthanum deficient lanthanum manganite La 1−x MnO 3±δ up to 1273 K were reported by various authors [6][7][8][9].…”
Section: Introductionmentioning
confidence: 97%
“…However, on prolonged use of the fuel cell, poorly conducting phases such as SrZrO 3 may form at the interface of cathode and YSZ (yttria stabilized zirconia) electrolyte. Hence recently an interest is generated to study rare earth manganites without aliovalent doping at the lanthanum site in LaMnO 3 [5]. Detailed investigations on polymorphic forms, defect structure, magnetism, ionic conducting properties and catalytic behaviour of lanthanum deficient lanthanum manganite La 1−x MnO 3±δ up to 1273 K were reported by various authors [6][7][8][9].…”
Section: Introductionmentioning
confidence: 97%
“…Among rare earth manganites, lanthanum manganite has been studied extensively due to its wide range of nonstoichiometry resulting from mixed valances of manganese, which governs some of the physical properties. Several recent studies [4][5][6][7][8] have shown that there are at least four forms La 1−x MnO 3+δ , two orthorhombic, one rhombohedral and one cubic depending on oxygen stoichiometry but not on the cationic deficiency. Shu et al [9] have studied the high temperature phase transition of orthorhombic La 0.95 MnO 3 in air from room temperature to 1273 K. They have also observed two phase transitions, first from orthorhombic to rhombohedral (373-473 K) and second from rhombohedral to cubic (973-1273 K).…”
Section: Introductionmentioning
confidence: 99%